Kindergarten teachers’ perceptions of conditions for professional learning communities in Dammam, Saudi Arabia - Bin Ateeq, Asma Mohammed (Kansas State University, 2018)
The Professional Learning Community (PLC) is a model of collaborative professional development that involves teachers and administrators working together on an ongoing basis to develop shared visions, plans, goals, resources, and ideas in order to increase student learning. Research indicates that students in schools with teacher PLCs are significantly more academically successful than students in schools that do not have PLCs. The teachers in PLCs also report positive benefits. There are six equally important dimensions of an effective PLC: shared and supportive leadership; shared beliefs, values and vision; collective learning and application of learning; supportive conditions (both structural and relational), and shared personal practice (Hord & Sommers, 2008). The purpose of this study was to explore perceptions of kindergarten teachers through the use of a survey and to further explore how two kindergarten teachers in Dammam describe their experiences of the conditions needed for implementing PLCs in their schools through personal interviews. The design of this study was mixed methods research conducted via a survey (questionnaire) and personal interviews. The data analysis suggests that the overall PLC dimensions in kindergartens in Dammam are somewhat supportive of PLCs. In the quantitative analysis, the mean scores ranged from 2.88 for Shared and Supportive Leadership to 3.15 for Shared Personal Practice (on a scale of 0-5). In the qualitative analysis, the participants’ descriptions of their experiences indicated that Shared Values and Vision was the weakest dimension. Keywords: professional learning community, kindergarten, conditions for PLC, Dammam, Saudi Arabia
Keywords: Professional learning community; Kindergarten; Conditions for PLC; Dammam; Saudi Arabia